2003
DOI: 10.1074/jbc.m209343200
|View full text |Cite
|
Sign up to set email alerts
|

The Two Photocycles of Photoactive Yellow Protein fromRhodobacter sphaeroides

Abstract: Photoactive yellow protein (PYP)1 is a photoreceptor that has been found in several purple bacteria (1). The first, and so far best studied example for this group of blue light receptors, was found in Ectothiorhodospira halophila (E-PYP) (2). The chromophore, responsible for the photophysical properties of PYP, is 4-hydroxy-cinnamic acid that is bound to Cys-69 via a thiolester linkage (3, 4). The crystal structure of this small protein, consisting of 125 amino acids, has been solved to 1.4-Å resolution (5) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 45 publications
(64 reference statements)
3
24
0
Order By: Relevance
“…Finally, the lifetime of the pB state varies by more than 6 orders of magnitude—from 1 ms in Rb. sphaeroides (41) to longer than an hour in S. ruber . This raises the question as to how different members of the PYP family tune the p CA absorbance maximum, p CA p K a and pB lifetime over a wide array of values to achieve biologically functional values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the lifetime of the pB state varies by more than 6 orders of magnitude—from 1 ms in Rb. sphaeroides (41) to longer than an hour in S. ruber . This raises the question as to how different members of the PYP family tune the p CA absorbance maximum, p CA p K a and pB lifetime over a wide array of values to achieve biologically functional values.…”
Section: Resultsmentioning
confidence: 99%
“…p CA in the PYP from T. tepidum exhibits an even higher p K a —10.2 (39). Also, the lifetime of the pB state varies significantly among the PYPs: from 1 ms for the PYPs from the two Rhodobacter species (10,40,41) to minutes for the PYPs from R. centenum and T. tepidum and the second PYP from H. halophila (9,12,39).…”
Section: Introductionmentioning
confidence: 99%
“…Haker et al . created a model of Rb. sphaeroides PYP in which they also noted increased exposure of the chromophore due to T50A and M100G substitutions.…”
Section: Discussionmentioning
confidence: 99%
“…capsulatus and Rb. sphaeroides PYP than in the prototypical Hhal PYP (13,16). Interestingly, both Rcaps and Rsph PYP have an M100G substitution in their sequences, which would seem to demand an order of magnitude slower recovery.…”
Section: Introductionmentioning
confidence: 96%
“…For PYP from Rb. sphaeroides it has been shown that, upon excitation, the species at 360 can also enter a photocycle, independent from the photocycle of the 446 nm species (Haker et al 2003). Furthermore, in both proteins, the ground state is recovered after photoexcitation ∼100-fold faster than in PYP from H. halophila.…”
Section: Photo-activation In the Different Xanthopsins Comparedmentioning
confidence: 94%